The Ict in the Mypes of the culinary sector in Tingo Maria city, 2017 - Aguirre-Caldas, Johann (2019)
This investigation contains the systematized report on the Influence of the ICT in the benefit of the MSEs of the culinary sector in Tingo María city, 2017, and it is a contribution to the scientific research. The objective was to analyze the way in which the use of ICT influence in improving the service satisfaction of the MSEs in the culinary sector in Tingo María city. The purpose of the applied method had the purpose was the analysis and interpretation of the results, where the descriptive - correlational design of non - experimental type was used, we worked with a sample of 15 restaurants, selected by the type of convenience sampling or by intentional selection, who answered the questionnaire. When we analyze the results it is concluded that the interaction between the forms of ICT tools and satisfaction it influences the modernization of the restaurants in Tingo María with the implementation of ICT. In this way it generates more clients, more income and more prestige for the company since it shows that the value of P = 0.185 which indicates a high expository relation that is greater than 0.05, accepting Ho therefore there is evidence of positive correlation between the variables.